Getting to specifics: Bangladesh’s evolving nutrition policies - Davis, Peter; Nisbett, Nicholas; Akhtar, Nazneen; Yosef, Sivan (International Food Policy Research Institute, 2016)
REMARKABLE IMPROVEMENTS IN welfare and human development indicators in Bangladesh—including a notable reduction in the poverty headcount—have accompanied recent economic growth.1 Some aspects of nutrition have been part of this success story. For example, the percentage of underweight children declined by 1.1 percent per year and stunting rates declined by 1.3 percent per year between 1997 and 2007.2 And this trend has continued, with rates of child stunting falling to 36 percent in 2014 (Figure 12.1). Other countries may have experienced shorter, quicker reductions, but the Bangladesh story reflects “one of the fastest prolonged reductions in child underweight and stunting prevalence in recorded history.